ACIDENTE DE TRABALHO: ASPECTOS JUSLABORAIS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article aims to analyze the occurrence of accidents at work, as well as the employer's liability, by studying the emergence, circumstances, definitions, main characteristics, species, regulations and discuss the importance of Safety and Occupational Medicine in risk management and accident prevention, as well as in the supervision of such preventive measures to reduce the statistics and occurrence of such accidents in the professional environment. It aims to investigate the specific norms and legislation in force, as well as the existing gaps in the legal system and thus highlight the consequences of the institute occupational accident, which is a genus, of which occupational diseases and work-related diseases are part as species, in the Labor Law. It is important to highlight the points that were changed by Law No. 13,467/2017 (Labor Reform), showing the movement of the social mechanism that accidents at work cause and, simultaneously, the economic consequences generated to all involved.